Role of transvaginal ultrasound in evaluation of ureteral involvement in deep infiltrating endometriosis - P. Carfagna; Carlo De Cicco Nardone; Alessandra Nardone; A. C. Testa; Giovanni Scambia; Riccardo Marana; Fiorenzo De Cicco Nardone (2017)
ABSTRACT Objective To assess whether routine examination of the ureters on transvaginal sonography (TVS) can identify reliably potential silent ureteral involvement by endometriosis and should therefore be recommended in all patients with deep infiltrating endometriosis (DIE). Methods This was a prospective study of 200 consecutive patients scheduled for surgery for DIE, evaluated between January 2012 and December 2014 at a tertiary endometriosis center at Fondazione Policlinico Universitario A. Gemelli, Rome, Italy. Routine TVS, abdominal ultrasound and gynecological examination were performed within 3 months before surgery, and patient history, signs and symptoms were recorded. Surgical and histological findings were compared with the preoperative ultrasonographic diagnosis. The main outcome of interest was the presence of ureteral dilatation or hydronephrosis caused by endometriosis. Results Of 200 patients with DIE, associated ureteral dilatation was diagnosed on TVS in 13 (6.5%) cases. Ureteral involvement was confirmed intraoperatively in all 13 cases by detection of ureteral dilatation caused by endometriotic tissue surrounding the ureter and causing stenosis. Of the 13 patients with ureteral dilatation, renal ultrasound detected six (46.2%) cases of hydronephrosis. Mean duration of visualization and study of dilated ureters was 5 min (range, 3–9 min). Ureteric diameter was ≥ 6 mm in all cases of ureteral dilatation, with a median diameter of 6.9 mm (range, 6–18 mm). Both ureters were identified on TVS in all 200 patients with DIE. Conclusions Our study confirms a relatively high incidence of ureteral involvement in patients with DIE. TVS appears to be a reliable tool for the diagnosis of ureteral involvement and, additionally, it allows the detection of both the level and degree of obstruction. Our findings confirm that TVS examination is an accurate non‐invasive diagnostic tool for the detection of ureteral involvement by endometriosis. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.